Assembling Color on the Nanoscale: Multichromatic Switchable Pixels from Plasmonic Atoms and Molecules. Issue 18 (17th March 2016) - Chen, Tianhong; Reinhard, Björn M.
Abstract : Nanoparticles of different materials, shapes, and sizes are integrated into plasmonic atoms and molecules of defined shape and location through sequential directed self‐assembly following a single patterning step. A rational tuning of the emitted color across the visible range of the electromagnetic spectrum and switchable polarization properties are demonstrated. Self‐assembled plasmonic pixels provide tunable, stable, and switchable optical responses.